Polysaccharide extract from Rosa laevigata fruit attenuates inflammatory obesity by targeting redox balance and gut interface in high-fat diet-fed rats - Xuejiao Zhang; Chenzhong Jin; Han Liu; Yihong Hu; Yunyun Zhou; Weiguo Wu; Si Qin (Food Science and Human Wellness)
Low-molecular-weight polysaccharides (RLPs) extracted from Rosa laevigata fruits showed multiple biofunctions in Asia. This study aimed to investigate its anti-inflammatory obesity effect in high-fat diet-fed rats and further elucidated the underlying molecular mechanism by multi-omics methods. The results showed that RLPs administration had significantly restored immune organ indexes and reduced body weight gain. RNA-seq revealed that the effect of RLPs was partially attributed to its regulation on PPARs signaling by increasing the expressions of Scd, Acox3 and Hmgcs2, and on other redox-related pathways by decreasing the expressions of Cyp2e1, Il1-r1 and Lbp. Moreover, 16S rRNA sequencing coupled with metagenome sequencing showed that RLPs had significantly reduced the ratio of Firmicutes/Bacteroidetes from 8.01 to 2.37, and significantly increased the relative abundances of Alistipes, Prevotella, and Akkermansia from 0.36 %, 1.10 % and 2.61 % to 0.65 %, 2.37 % and 4.42 %, respectively. Spearman correlation analysis result indicated that the abundances of Lachnospiraceae, Prevotella and Bacteroidales were significantly negatively correlated with obesity phenotype, liver function and inflammatory factors. These results revealed that RLPs exerted significant anti-inflammatory obesity property partially via regulation on gut microbiota interface and the redox balance. Therefore, RLPs could be a promising functional food resource with the potential for redox imbalance-related diseases chemoprevention.